Produção e avaliação de nanoemulsão catiônica como possível vetor não-viral para pIRES2-EGFP - Silva, André Leandro (2013)
Gene therapy is based on the transfer of exogenous genetic material into cells or tissues in order to correct, supplement or silencing a particular gene. To achieve this goal, efficient vehicles, viral or non-viral, should be developed. The aim of this work was to produce and evaluate a nanoemulsion system as a possible carrier for no-viral gene therapy able to load a plasmid model (pIRES2-EGFP). The nanoemulsion was produced by the sonication method, after been choose in a pseudo-ternary phase diagram build with 5 % of Captex 355®, 1.2 % of Tween 80®, 0.8 % of Span 80®, 0.16% of stearylamine and water (to 100 %). Measurements of droplet size, polydispersity index (PI), zeta potential, pH and conductivity, were performed to characterize the system. Results showed droplets smaller than 200 nm (PI < 0.2) and zeta potential > 30 mV. The formulation pH was near to 7.0 and conductivity was that expected to oil in water systems (70 to 90 μS/s) A scale up study, the stability of the system and the best sterilization method were also evaluated. We found that the system may be scaled up considering the time of sonication according to the volume produced, filtration was the best sterilization process and nanoemulsions were stable by 180 days at 4 ºC. Once developed, the complexation efficiency of the plasmid (pDNA) by the system was tested by agarose gel electrophoresis retardation assay.. The complexation efficiency increases when stearylamine was incorporated into aqueous phase (from 46 to 115 ng/μL); regarding a contact period (nanoemulsion / pDNA) of at least 2 hours in an ice bath, for complete lipoplex formation. The nanoemulsion showed low toxicity in MRC-5 cells at the usual transfection concentration, 81.49 % of survival was found. So, it can be concluded that a nanoemulsion in which a plasmid model was loaded was achieved. However, further studies concerning transfectation efficiency should be performed to confirm the system as non-viral gene carrier